Some Aspects and Generalisations of the Theory of Discrimination - Simkin, C. G. F. (Review of Economic Studies, 1947)
Journal Article Some Aspects and Generalisations of the Theory of Discrimination Get access C. G. F. Simkin C. G. F. Simkin Auckland, N.Z. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 15, Issue 1, 1947, Pages 1–13, https://doi.org/10.2307/2295922 Published: 01 April 1947